2023
DOI: 10.3390/metabo13020173
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Premium Civet Luwak Bio-Transformed Coffee Compared with Conventional Coffee Types, as Analyzed Using Chemometric Tools

Abstract: Luwak (civet) coffee is one of the most precious and exotic coffee commodities in the world. It has garnered an increasing reputation as the rarest and most expensive coffee, with an annual production. Many targeted analytical techniques have been reported for the discrimination of specialty coffee commodities, such as Luwak coffee, from other ordinary coffee. This study presents the first comparative metabolomics approach for Luwak coffee analysis compared to other coffee products, targeting secondary and aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…11 This instrument has also been used to identify civet coffee metabolites dissolved in methanol. 12 The findings revealed that civet coffee had higher levels of fatty acids than regular coffee. Easy sample preparation is one of the fundamental advantages of NMR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 This instrument has also been used to identify civet coffee metabolites dissolved in methanol. 12 The findings revealed that civet coffee had higher levels of fatty acids than regular coffee. Easy sample preparation is one of the fundamental advantages of NMR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 96%
“…This method has successfully identified and quantified several metabolites in green civet coffee beans without separation, such as alanine, asparagine, GABA, malic acid, chlorogenic acid, quinic acid, choline, sucrose, caffeine, and trigonelline . This instrument has also been used to identify civet coffee metabolites dissolved in methanol . The findings revealed that civet coffee had higher levels of fatty acids than regular coffee.…”
Section: Introductionmentioning
confidence: 99%